EXPOSING THE TRUE ARGUMENT, A STUDENT’S RESPONSE TO DR WILLEM GRAVETT: ‘PERICLES SHOULD LEARN TO FIX A LEAKY PIPE’* (The Pretoria Student Law Review, 2021)
The purpose of this article is not to come to the defence of the individual academics that Gravett has decided to criticise, for they can surely defend themselves. I wish only to make clear the importance of the work they are doing as a way to point critics of the current system away from their colleagues and onto the legal education system at large, which is the real obstacle standing in the way of Trial Advocacy. This article superficially only argues that the there is no real threat to a destruction of the antithesis between theory and practice and that few oppose this position. Subsequent articles will hopefully answer to the underlying concerns Gravett poses to the critical thinking, constitutionalism and transformative constitutionalism are possibly breaking down the rule of law etc; WH Gravett ‘Pericles should learn to fix a leaky pipe — Why trial advocacy should become part of the LLB curriculum (Part 1)’ (2018) 21 Potchefstroom Electronic Law Journal (PER/PELJ) at 4.
Keywords: WILLEM GRAVETT; legal education system; Trial Advocacy; theory and practice; critical thinking; transformative constitutionalism; constitutionalism